Integrated distributed feedback lasers and electroabsorption modulators fabricated using helium-plasma-assisted indium phosphide defect induced quantum well intermixing - Letal, Gregory (My University, 2000)
An integrated DFB laser and electroabsorption modulator was fabricated by using a novel quantum-well-intermixing technique that uses the defects from a layer of InP grown by He-plasma-assisted gas source molecular beam epitaxy (He*-InP). This is the first investigation into the He*-InP defect induced intermixing, and the first time a device has been fabricated by using this technique. The first part of this thesis outlines the first investigation into the effects of defects within a layer of He*-InP on annealing-induced quantum-well intermixing. Such a layer can be used to either decrease or increase the total amount of intermixing depending upon the placement of the He*-InP layer relative to the QW and the thickness of the layer. When the layer is far from the QW (∼0.5μm ), the total amount of intermixing is decreased. When the layer is close to the QW, the total amount of intermixing can be increased as well as being accompanied by a reduction of the photoluminescence intensity. The main benefit of this intermixing technique is that, unlike dielectric-enhanced intermixing, it is possible to regrow over material that has been intermixed by the He*-InP defect. The He*-InP defect-induced-intermixing technique has been applied to the fabrication of an integrated electroabsorption modulator and a distributed feedback laser. The techniques developed to fabricated the integrated device are discussed in detail in the second part of the thesis, followed by the device results. The device characteristics vary with device geometry. For example, the extinction ratios range from 9-16dB for voltage of 3V applied to a 400μm modulator due to the variation of the lasing wavelength with ridge width (for a 3QW structure). The threshold currents of discrete, 600μm long DFB lasers ranged from 18 to 35mA depending on its ridge width and where on wafer it was taken from.
Keywords: Engineering Physics; Engineering Physics